Assisted living : needs, practices, and policies in residential care for the elderly - Zimmerman, Sheryl, 1957-; Sloane, Philip D.; Eckert, J. Kevin; Lawton, M. Powell (Mortimer Powell), 1923-2001 (Johns Hopkins University Press, 2001)
This text examines the evolving field of residential care and focuses on national issues of regulation, reimbursement and staffing. The book describes assisted-living facilities, those living in them, their needs and how services vary.